2018
DOI: 10.4103/jrms.jrms_344_17
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRB1 gene polymorphisms in Iranian children with Henoch-Schönlein purpura

Abstract: Background:People of all ages can suffer from Henoch-Schönlein purpura (HSP), but it is the most common vasculitis in childhood. The most important involving gene is located on chromosome 6p21.3, a region coding for human leukocyte antigens (HLAs). Among HLA genes, because of the high rate of polymorphisms, HLA-DRB1 is estimated to have a strong association with HSP. In this study, we aimed to assess the association of HLA-DRB1 alleles with HSP in Iranian children.Materials and Methods:This study consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Finally, both the meta-analysis and the RPE method demonstrated a lack of correlations between the other HLA genetic allele groups and LADA. We did not find any associations of HLA-DQB1*03 , HLA-DQB1*04 , HLA-DRB1*10 , HLA-DRB1*11 , HLA-DRB1*14 , HLA-DRB1*15 , and HLA-DRB1*16 with the risk of LADA when using either method, although some studies reported that these polymorphisms may be related to other autoimmune diseases, such as multiple sclerosis (MS) [43], Henoch–Schönlein purpura (HSP) [44], and T1DM [45].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, both the meta-analysis and the RPE method demonstrated a lack of correlations between the other HLA genetic allele groups and LADA. We did not find any associations of HLA-DQB1*03 , HLA-DQB1*04 , HLA-DRB1*10 , HLA-DRB1*11 , HLA-DRB1*14 , HLA-DRB1*15 , and HLA-DRB1*16 with the risk of LADA when using either method, although some studies reported that these polymorphisms may be related to other autoimmune diseases, such as multiple sclerosis (MS) [43], Henoch–Schönlein purpura (HSP) [44], and T1DM [45].…”
Section: Discussionmentioning
confidence: 99%
“…A common theory supported experiments suggests the role of the Cytochrome c Oxidase as a photoacceptor and key enzyme of respiratory chain mitochondria in PBM [38]. Cytochrome c Oxidase plays a key role in mitochondrial respiration and electron transport and contains a binuclear copper center and heme binuclear center [51] making this enzyme a uniquely available and responsive target for NIR. Cytochrome c Oxidase dysfunction is associated with increased NO production.…”
Section: Introductionmentioning
confidence: 99%